Is multifocality a prognostic factor in childhood hepatoblastoma?. Issue 9 (23rd April 2014) - Saettini, Francesco; Conter, Valentino; Provenzi, Massimo; Rota, Matteo; Giraldi, Eugenia; Foglia, Carlo; Cavalleri, Laura; D'Antiga, Lorenzo
Abstract Background The aim of this study was to assess the prognostic value of multifocality and the effectiveness of two different therapeutic strategies in patients with newly diagnosed hepatoblastoma. Procedures Between 1998 and 2011, 31 patients diagnosed with hepatoblastoma were referred to Ospedale Papa Giovanni XXIII, Bergamo, Italy. Patients were stratified according to SIOPEL protocols into high‐risk (HR if AFP <100 ng/mL and/or PRETEXT IV and/or vascular invasion and/or extra‐hepatic intra‐abdominal disease and/or metastases) and standard‐risk (SR, all others). The patient data we evaluated were: multifocality; patient age; gender; platelet count; AFP level at diagnosis, during treatment and follow‐up; histotype; gestational age; birth weight; surgery (either resection or transplantation) and chemotherapy regimen adopted before and after surgery. The outcome measures were event free survival (EFS) and overall survival (OS); survival curves were estimated according to Kaplan–Meier. Results EFS and OS were associated significantly with multifocality (3‐year EFS 40% vs. 95%, P = 0.006; 3‐year OS 42% vs. 95%, P = 0.004). Multivariate analysis demonstrated that multifocality predicts lower EFS (hazard ratio 10.01, P = 0.007). Other factors at diagnosis did not reach statistical significance. A marked treatment dependent improvement was associated with intensive chemotherapy given both before and after liver transplantation (P = 0.06). Conclusions Patients diagnosed with multifocal tumors had lower EFS levels. Multifocality should be taken into account for future stratification and further studied to assess genetic profile, immunochemistry and prognostic role. Pediatr Blood Cancer 2014;61:1593–1597. © 2014 Wiley Periodicals, Inc.